2020
DOI: 10.1103/physrevb.101.144431
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of spin-transfer torques for antiferromagnetic domain walls

Abstract: We numerically compute current-induced spin-transfer torques for antiferromagnetic domain walls, based on a linear response theory in a tight-binding model. We find that, unlike for ferromagnetic domain wall motion, the contribution of adiabatic spin torque to antiferromagnetic domain wall motion is negligible, consistent with previous theories. As a result, the non-adiabatic spin-transfer torque is a main driving torque for antiferromagnetic domain wall motion. Moreover, the non-adiabatic spin-transfer torque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 84 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…This large β is attributed to the spin-mistracking process 102,103 , which was originally introduced to describe an enhanced β in ferromagnets, when the spin precession length is longer than the DW width. A recent theory showed that spin mistracking is more pronounced in antiferromagnets than in ferromagnets 104 , in line with the long λ c in antiferromagnetically ordered systems. Quantitatively, however, the large β/α ratio is poorly understood at this moment, and demands further theoretical studies on spin transport in compensated ferrimagnets.…”
Section: Spin Transport In Compensated Ferrimagnetsmentioning
confidence: 73%
“…This large β is attributed to the spin-mistracking process 102,103 , which was originally introduced to describe an enhanced β in ferromagnets, when the spin precession length is longer than the DW width. A recent theory showed that spin mistracking is more pronounced in antiferromagnets than in ferromagnets 104 , in line with the long λ c in antiferromagnetically ordered systems. Quantitatively, however, the large β/α ratio is poorly understood at this moment, and demands further theoretical studies on spin transport in compensated ferrimagnets.…”
Section: Spin Transport In Compensated Ferrimagnetsmentioning
confidence: 73%
“…In FMs, torque contributes to both domain-wall depinning and steady motion below Walker breakdown even though it is typically small 23 . On the other hand, the FIs 33 and collinear AFMs 34 , 35 were reported to have much larger β torque contributions. Similarly, a significant β torque contribution could be accounting for current-driven fast MODW motion.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, AFs are immune to perturbations by magnetic fields. These features may enable resilient AF-based memory devices with picosecond switching times [5,11,12], nanoscale oscillators operating in the T Hz frequency range [13][14][15], and ST-driven AF domain wall motion with extremely high velocities [6,16].…”
mentioning
confidence: 99%